(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: WHO and the International Federation of Gynecology and Obstetrics recognise the words "Post maturity," "Post term," "Postdate" and "Prolonged pregnancy" to describe pregnancies that continue beyond their intended end points (Expected date of delivery). As much as 10% of pregnancies become more complicated due to a pregnancy that lasts longer than expected and this poses risks to both the mother and the unborn child. The purpose of the study is to observe of medical induction of labour in post-dated pregnancy. Materials and methods: This prospective observational study was conducted in the Department of Obstetrics and Gynecology, IAHS, USTC, Chattogram, Bangladesh, from January to June 2022. 120 patients included in our study. Labour induction in post-dated pregnancy was performed only after appropriate assessment of the mother and foetus. The inclusion criteria were intact membrane, cephalic presentation, singleton pregnancies, low Bishop score in post-dated pregnancies. Absolute contraindications to induction of labour include contracted pelvis, placenta previa, unexplained vaginal bleeding, presentation other than head and previous caesarean section were excluded from the study. This study shows that the main method was gxytocin drip and second method was ARM+ oxytocin in drip, some cases induced by using oral prostaglandin and very few cases induced by vaginal prostaglandin. Results: During the study 21-31 years age group , 60.6% , 41.6% were in oxytonin drip followed by 38.3% were in ARM + Oxytonin drip, 14.1% were in misoprostol in oxytocin drip 30% were failed cases followed by in ARM + Oxytocin drip it was 25%, in misoprostol it was 14.2%. Majority had Spontaneous vaginal delivery followed by 15% had Delivery by Caesarean section and 10% had Delivery with the aid of Forceps, 13.3% had foetal distress and 5% had unfavourable cervix. 75% were healthy baby and 20% were distress baby. Conclusion: Successful birth outcomes are strongly correlated with labor starting at the optimal time. An accurate diagnosis of postdatism is crucial. Mothers” worries and issues related postdatism may be reduced with the help of sound guidance and close observation from healthcare providers. Due to technical constraints in foetal monitoring and oxytocin titration, caesarean section after used to terminate most post-dated pregnancies in various hospitals throughout the nation. When a mature a mature cervix and optimal fetal presentation are present, including lobor seems to be safe for both the woman and the baby. JCMCTA 2025 ; 36 (2) : 125-130